Penerapan Metode Pembelajaran Jigsaw Pada Mata Pelajaran PAI Kelas 10 SMK Teknologi Informasi Karangtanjung Kebumen - Fatimatuzzakiyah, Dewi; Trisnawati, Oky Ristya (Tarbi: Jurnal Ilmiah Mahasiswa, 2025)
The objectives of this study are: (1) To identify the steps in implementing the Jigsaw method in the Islamic Religious Education (PAI) subject for Grade 10 at SMK Teknologi Informasi Karangtanjung Kebumen; and (2) To identify the supporting and inhibiting factors in the application of the Jigsaw method in the same subject and setting. This research is a qualitative study. The subjects are the Islamic Education teacher and Grade 10 students at SMK TI. The research method used is descriptive. Data collection techniques include observation, interviews, and documentation. Data analysis was carried out through data condensation, data display, and drawing conclusions. The results show that: (1) The learning process consists of three main stages: opening, core, and closing activities. The teacher begins by providing motivation and an introductory activity, then implements the Jigsaw method based on pre-arranged steps. In the final stage, the teacher provides a summary and conducts an evaluation through a written test. This method has proven effective in enhancing student learning outcomes; (2) Supporting factors include increased student participation and responsibility, improved communication and social skills, equal understanding of the material, and an enjoyable learning experience. Meanwhile, the inhibiting factors include limited time, inadequate facilities, limited teacher competence, differences in students' academic abilities and participation, and the incompatibility of some materials with the Jigsaw method.